Multiparametric Optical Bioimaging Reveals the Fate of Epoxy Crosslinked Biomeshes in the Mouse Subcutaneous Implantation Model - Elagin, Vadim; Kuznetsova, Daria; Grebenik, Ekaterina; Zolotov, Denis A.; Istranov, Leonid; Zharikova, Tatiana; Istranova, Elena; Polozova, Anastasia; Reunov, Dmitry; Kurkov, Alexandr; Shekhter, Anatoly; Gafarova, Elvira R.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Biomeshes based on decellularized bovine pericardium (DBP) are widely used in reconstructive surgery due to their wide availability and the attractive biomechanical properties. However, their efficacy in clinical applications is often affected by the uncontrolled immunogenicity and proteolytic degradation. To address this issue, we present here in vivo multi-parametric imaging analysis of epoxy crosslinked DBPs to reveal their fate after implantation. We first analyzed the structure of the crosslinked DBP using scanning electron microscopy and evaluated proteolytic stability and cytotoxicity. Next, using combination of fluorescence and hypoxia imaging, X-ray computed microtomography and histology techniques we studied the fate of DBPs after subcutaneous implantation in animals. Our approach revealed high resistance to biodegradation, gradual remodeling of a surrounding tissue forming the connective tissue capsule and calcification of crosslinked DBPs. These changes were concomitant to the development of hypoxia in the samples within 3 weeks after implantation and subsequent induction of angiogenesis and vascularization. Collectively, presented approach provides new insights on the transplantation of the epoxy crosslinked biomeshes, the risks associated with its applications in soft-tissue reconstruction and can be transferred to studies of other types of implants.